(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The aim of the present investigation is to study the effect of different simulated solutions onwear behavior, chemical properties and ion release of Ti-6Al-4V alloy which used in humanbody. For this purpose three solutions have been used (Hank's solution, 0.9NaCl andartificial saliva). The corrosion properties of Ti-6Al-4V implant alloy were examined at37ºC by using electrochemical techniques, such as the potentiodynamic method and opencircuit potential (OCP). The electrochemical corrosion characteristics of Ti-6Al-4V implantalloys in three biological solutions were measured in terms of the corrosion potential (Ecorr)and the corrosion current density (icorr ).Wear behavior was investigated by using pin-ondisctribometers at human temperature under different loads (10,15,20)N. The wear testconsisted of measuring the weight loss of samples. The metal ion release of base andalloying element by immersed specimens into various solutions for 7 days (168 hours) at37ºC. The result found that the Ti6Al4V implant alloy in three biological solutions exhibiteda characteristic of a good behavior. The superior corrosion resistance these alloy whichcurrent density measured in (nA/cm2). The weight loss of samples by wear test increase withincrease load and time. After applied heat treatment, about 40% enhancement in the wearbehavior of alloy. The quantity of Al element metal release of implant alloy with variationfluids which increase with decrease the value of pH and little amount of vanadium elementin hank's solution.